Netherlands Heart Journal
The scope of the Netherlands Heart Journal is to contribute to the national and international literature by publishing scientific papers in the field of cardiovascular medicine. It also provides a platform for Continuing Medical Education for cardiologists and those in training for the speciality of cardiology in the Netherlands. The Netherlands Heart Journal is made available to cardiologists, cardiologists in training, cardiopulmonary surgeons, cardiopulmonary surgeons in training, internists and paediatric cardiologists. The journal is the official journal of the Netherlands Society of Cardiology.